m6A Modification: A Double-Edged Sword in Tumor Development - Gao, Runnan; Ye, Mujie; Liu, Baihui; Wei, Meng; Ma, Duan; Dong, Kuiran (Frontiers in Oncology, 2021)
Modification of m6A, as the most abundant mRNA modification, plays diverse roles in various biological processes in eukaryotes. Emerging evidence has revealed that m6A modification is closely associated with the activation and inhibition of tumor pathways and it is significantly linked to the prognosis of cancer patients. Aberrant reduction or elevated expression of m6A regulators and of m6A itself have been identified in numerous tumors. In this review, we give a description of the dynamic properties of m6A modification regulators, such as methyltransferases, demethylases, and m6A binding proteins, and indicate the value of the balance between these proteins in regulating the expression of diverse genes and the underlying effects on cancer development. Furthermore, we summarize the ‘dual edged weapon’ role of RNA methylation in tumor progression and discuss that RNA methylation can not only result in tumorigenesis, but also lead to suppression of tumor formation. In addition, we summarize the latest research progress on small-molecule targeting of m6A regulators to inhibit or activate m6A. These studies indicate that restoring the balance of m6A modification via targeting specific imbalanced regulators may be a novel anti-cancer strategy.